Edukasi Mencegah Stunting Dengan Oral Motor Exercise di Pos Balita Puskesmas Banyuanyar Surakarta - Komang Dian Utami Chandra Dinata; Suryo Saputra Perdana; Seliana Sinta Debi (Jurnal Rumpun Ilmu Kesehatan, 2024)
Stunting is a growth disorder caused by inappropriate nutritional disorders, where the prevalence of stunting in Indonesia reaches 29.7% and Surakarta is ranked second in the number of stunting cases in Central Java with 1,050 cases. Banyuanyar sub-district, toddlers who experience nutritional disorders are 37.5% of the total number of toddlers, namely 24 people. The aim of conducting outreach activities in the form of education is to be a promotive and preventive method in preventing stunting by providing oral motor exercises so that toddlers are stimulated to breastfeed, chew and swallow food. The method used was education in the form of counseling and distribution of leaflets to parents or caregivers of toddlers at the toddler post RW 03 Banyuanyar Community Health Center. The results obtained from measurements were an increase in understanding using pretest and posttest questionnaires, namely there was a significant increase in understanding related to counseling with an average pretest score of 15 and an average posttest score of 90.